IMPROVEMENT OF PICK-UP ROUTES FOR AN INTERNATIONAL SHIPPING ENTERPRISE BY USING A HEURISTIC METHOD - Durán-Mendez, Mario-Alberto; Caballero-Morales, Santiago-Omar; Martínez-Flores, José-Luiz; Cano-Olivos, Patricia (Revista Latino-Americana de Inovação e Engenharia de Produção, 2016)
Route design is an important factor for the management of supply and logistics operations required by production processes. In this work the re-design of pick-up/delivery routes for an international shipping enterprise was performed to improve vehicle utilization for pick-up/delivery operations and reduce transportation time. The re-design of the routes was accomplished by using a random heuristic method. As a result, it was obtained that pickup/delivery for all clients can be performed with a small number of vehicles. Also, vehicle utilization can be maximized over 90.00% with a significant reduction in total transportation time which leads to decrease operational cost. The additional available time then can be used to cover a higher number of clients, increasing the presence of the enterprise in the market.